EKONOMI PERANTAU MINANGKABAU DI PASAR BAWAH KECAMATAN BANGKO KABUPATEN MERANGIN TAHUN 1999-2020 - Rissa Afrilia Rosanti; Azmi Fitrisia (Jurusan Sejarah FIS UNP, 2022)
This study examines the economic life of Minangkabau migrants in Pasar Bawah, Bangko District, Merangin Regency in 1999-2020. The research problems are formulated as follows: (1) How did Minangkabau traders arrive in Pasar Bawah, (2) How did the Minangkabau trade economy develop in Pasar Bawah during 1999-2020. This writing aims to reveal the background of the Minangkabau people who migrated to Pasar Bawah Bangko, Merangin Regency and the economic situation of Minangkabau overseas in Pasar Bawah Bangko.. Based on the research results it is known that; First: Pasar Bawah Bangko is one of the markets located in Pasar Bangko Village, Bangko District, Merangin Regency which is part of Jambi Province, because the area is close to the border of South Persisir and Dharmasraya regions, and the area is a new area due to the division of districts between Sarolangun dan Regency and Sarolangund Regency. Merangin became a new field for trading. Second: Minangkabau overseas trading activities are diverse, ranging from trading in clothes, basic necessities, accessories, shoes-sls, vegetables, and others. Keywords: Migrants, Traders, Ethnic Minangkabau